Implementasi Dimensi Kreatif pada Proyek Penguatan Profil Pelajar Pancasila - Yuniarti, Rizkia; Hamzah, Amir; Febrieanitha Putri, Yecha; Dewi, Kurnia; Marlina, Leny (UIR PRESS, 2024)
The Pancasila Student Profile is a graduate profile designed to help children develop the characters needed to become competent. Furthermore, it is hoped that this Pancasila student profile can help children uphold the values ​​of Pancasila. The aim of this research is to determine the application of the creative dimension in the project to strengthen the profile of Pancasila students at Kindergarten Kemala Bhayangkari 01 Palembang. This research uses a qualitative approach with the aim of describing how the creative dimension is implemented in the project to strengthen the profile of Pancasila students at Kindergarten Kemala Bhayangkari 01 Palembang Jalan. Bambang Utoyo Pakri Complex, Duku, District. Ilir Timur III, Palembang City. Data collection methods for this research are primary data and secondary data. Data collection techniques in this research are interviews, observation and documentation, while technical data analysis uses data reduction, data presentation and conclusion drawing or verification. The results obtained by Kindergarten Kemala Bhayangkari 01 Palembang have implemented the creative dimension of the project to strengthen the profile of Pancasila students well. In implementing the project to strengthen the profile of Pancasila students, it can be seen that the project implementation was carried out as it should. Where, teachers must really understand every project given to children. In co-curricular learning, teachers prepare activities related to children's creativity. Thus, strengthening the profile of Pancasila students in the creative dimension has been embedded in children. Expected aChildren can maintain and increase enthusiasm in the learning process and project activities to strengthen the Pancasila student profile so that they can grow the spirit of the Pancasila student profile in each of them.